Impact of social enterprise in West Java using the Platform Usaha Sosial (PLUS) database - Alif Zidan Fathurahman; Taufik Akbar; Tutik Rachmawati (Department of Government Science, 2024)
West Java is the province with the largest population in Indonesia, which is the basis for identifying social enterprises by sector. This research aims to uncover the social enterprise sectors developing in West Java and their impacts. This research uses a qualitative approach with the main data obtained through the PLUS database. The results show three main sectors with the highest number of social enterprises. The creative economy sector took the top spot with 19 social enterprises, which emerged in response to various social problems. The technology sector came in second with 12 social enterprises, which developed due to the need for digitalization in various areas of West Java. Meanwhile, with 11 social enterprises, the environmental energy sector developed in response to various environmental problems and low public awareness of environmental issues. The presence of social enterprises in West Java has a significant impact on three main aspects, namely social, economic, and environmental. This research emphasizes the importance of social enterprises in facing social and environmental challenges and their role in local economic development.